Effets des Actions des PTF et Echelle d’adaptation des Communautes Rurales aux Inondations dans le Doublet Karimama-Malanville (Benin, Afrique de L’ouest) - Yabi, Hervé; Sossou, Koffi Benoît; Akindele, Akibou A.; Balogoun, Roméo Ayéko; Ogouwale, Euloge (European Scientific Journal, ESJ, 2019)
To help flood victims, TFPs carry out emergency and recovery actions. This research analyzes the effects of TFP actions and the scale of adaptation of rural communities to floods in the Karimama-Malanville doublet. The methodological approach adopted revolves around the collection of data through documentary research, and field work with 200 respondents, the processing and analysis of results. Principal Component Analysis (PCA), Cramer’s Ki 2 and CrV tests are used for the statistical component. The results of this research show that during the emergency phase, TFPs such as CaritasBenin, Red Cross / Benin and CARE-Benin / Togo raise awareness (70.04%), the distribution of food (49.17 %), drugs (20.11%), sleeping materials (46.36%), household goods (25.69%), personal care products (73.17%), blankets (15.08 %) and school supplies (15.08%). In addition, during the recovery phase, Caritas-Benin, Red Cross / Benin, CARE-Benin / Togo and FAO distribute agricultural inputs (80.99%), sensitization (69.25%), relocation (49.15%), the distribution of building materials (29.04%), the construction of latrines (24.02%), the construction of boreholes (7.82%) and the vaccination of animals (2.23%). ), the construction of smoking rooms (2.23%) and the distribution of feeds and fry (1.67%) .The various emergency and recovery actions carried out by the TFPs have the protection against malaria, the reduction of cholera and the revival of economic activities in the Karimama-Malanville doublet. In general, TFP actions allow the rural communities of the Karimama-Malanville doublet to adapt to the new conditions of life imposed by the floods. Pour secourir les populations victimes des inondations, les PTF mènent les actions d’urgence et de relèvement. La présente recherche analyse les effets des actions des PTF et l’échelle d’adaptation des communautés rurales aux inondations dans le doublet Karimama-Malanville. La démarche méthodologique adoptée s’articule autour de la collecte des données à travers la recherche documentaire, les travaux de terrain auprès de 200 enquêtés, le traitement et l’analyse des résultats. L’Analyse en Composante Principale (ACP), les tests de Ki deux et de V de Cramer sont utilisés pour le volet statistique. Les résultats de cette recherche montrent que pendant la phase d’urgence, les PTF tels que Caritas-Bénin, Croix rouge/Bénin et CAREBénin/Togo font la sensibilisation (70,04 %), la distribution des vivres (49,17 %), des médicaments (20,11 %), des matériels de couchages (46,36 %), des biens domestiques (25,69 %), des produits d’hygiène (73,17 %), des couvertures(15,08 %) et fournitures scolaires (15,08 %). Par ailleurs, pendant la phase de relèvement, Caritas-Bénin, Croix rouge/Bénin, CAREBénin/Togo et FAO font la distribution des intrants agricoles (80,99 %), la sensibilisation (69,25 % ), le relogement (49,15 %), la distribution des matériaux de construction (29,04 % ), la construction des latrines (24,02 % ), la construction des forages (7,82 %), la vaccination des animaux (2,23 %), la construction des fumoirs (2,23 %) et la distribution des provendes et des alevins (1,67 %).Les différentes actions d’urgence et de relèvement menées par les PTF sont la protection contre le paludisme, la réduction du choléra et la relance des activités économiques dans le doublet Karimama-Malanville. En général, les actions des PTF permettent aux communautés rurales de cette localité de s’adapter aux nouvelles conditions de vie imposées par les inondations.